The potential of high resolution melting analysis (hrma) to streamline, facilitate and enrich routine diagnostics in medical microbiology - Ruskova, Lenka; Raclavsky, Vladislav (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2011)
BACKGROUND: Routine medical microbiology diagnostics relies on conventional cultivation followed by phenotypic techniques for identification of pathogenic bacteria and fungi. This is not only due to tradition and economy but also because it provides pure culture needed for antibiotic susceptibility testing. This review focuses on the potential of High Resolution Melting Analysis (HRMA) of double-stranded DNA for future routine medical microbiology. METHODS AND RESULTS: Search of MEDLINE database for publications showing the advantages of HRMA in routine medical microbiology for identification, strain typing and further characterization of pathogenic bacteria and fungi in particular. The results show increasing numbers of newly-developed and more tailor-made assays in this field. For microbiologists unfamiliar with technical aspects of HRMA, we also provide insight into the technique from the perspective of microbial characterization. CONCLUSIONS: We can anticipate that the routine availability of HRMA in medical microbiology laboratories will provide a strong stimulus to this field. This is already envisioned by the growing number of medical microbiology applications published recently. The speed, power, convenience and cost effectiveness of this technology virtually predestine that it will advance genetic characterization of microbes and streamline, facilitate and enrich diagnostics in routine medical microbiology without interfering with the proven advantages of conventional cultivation.
Keywords: genotypizační techniky; Bacterial Infections; Humans; DNA; lidé; Mycoses; Fluorescent Dyes; Genotyping Techniques; molekulární biologie; Molecular Biology; polymerázová řetězová reakce; Polymerase Chain Reaction; fluorescenční barviva; mykózy; bakteriální infekce